Kualitas Dadih Susu Kambing yang Diinkubasi pada Berbagai Macam Bambu - Meinar Dwi Sulinda Wijayanti; Imam Thohari; Purwadi Purwadi (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2016)
The objective of this research was to determine the best bamboo that can be used in the manufacture of dadih among apus, ori, betung and black bamboo based on acidity, protein content, pH and total of microorganisms of goat milk dadih. The materials used in this research was the dadih made from ingredients such as goat milk, banana leaf and bamboo. The methods used in this study was experiment with 4 treatments and 4 replications the data were analyzed by ANOVA, if there were a significantly different continued by Duncan's multiple range test. The result showed that the kind of bamboo gave highly significant different effect (p<0,01) on acidity, protein content, pH and total of microorganisms. According to the value of acidity, protein content, pH and total of microorganisms, it can concluded that the use of bamboo ori gave the best result in performance of dadih that the average of acidity was 0.37 ± 0.02%; protein content was 4.82 ± 0.13%; pH was 6.47 ± 0.05 and total of microorganisms was 6.298 ± 0.62072 Log cfu/mL.